INTRODUCTION OF NEW PARTS AND SAMPLES WITH HIGH PROTEIN, HIGH PRODUCTIVITY INDICATORS. (Archive of Conferences, 2021)
Chickpea is rich in nutrients and protein, and mixing 10-15% of wheat flour with bread improves nutrition and rapid digestion in the body. This article presents the indicators of yield and protein quality of pea varieties and samples grown in arable lands.